Kết quả bổ sung trong phân tích tài liệu từ để nghiên cứu mạng lưới đứt gãy Bắc Trung Bộ - Toàn, Đinh Văn; Bắc, Trịnh Việt (Vietnam Journal of Earth Sciences, 2001)
Using new results of magnetic data interpretation for the study of tectonic fault distribution in the nothern part ofVietnam central zone